Overexpression of the LcCUC2-like gene in Arabidopsis thaliana alters the cotyledon morphology and increases rosette leaf number - Wen,Shaoying; Li,Jiayu; Hao,Ziyuan; Wei,Lingmin; Ma,Jikai; Zong,Yaxian; Li,Huogen (PeerJ, 2022)
Background The unique ‘mandarin jacket’ leaf shape is the most famous trait of Liriodendron chinense and this characteristic gives L. chinense aesthetic and landscaping value. However, the underlying regulatory mechanism of genes involved in the leaf development of L. chinense has remained unclear. Methods Based on transcriptome data of leaves at different developmental stages from L. chinense, we identified differentially expression genes (DEGs) functioning in leaf development. A candidate gene named LcCUC2-like (LcCUC2L) had high similarity in sequence with Arabidopsis thaliana CUC2, and used for further research. We isolated the full-length LcCUC2L gene and its promoter from L. chinense. Subsequently, we analyzed the function of the LcCUC2L gene and its promoter activity via transformation into A. thaliana. Results In this study, we found that the LcCUC2L and AtCUC2 are homologous in sequence but not homologous in function. Unlike the role of AtCUC2 in leaf serration and SAM formation, the LcCUC2L mainly regulates cotyledon development and rosette leaf number. Histochemical β-glucuronidase (GUS) staining revealed that LcCUC2L was expressed in the cotyledons of A. thaliana seedlings, indicating that the LcCUC2L may play a role in cotyledon development. Ectopic expression of LcCUC2L resulted in long, narrow cotyledons without petioles, abnormal lamina epidermis cells and defective vascular tissue in cotyledons, and these results were consistent with the LcCUC2L expression pattern. Further analysis showed that overexpression of LcCUC2L also induced numerous rosette leaves. Also, LcCUC2L and other related genes showed a severe response in L. chinense by introducing exogenous auxin stimulation, partly revealed that LcCUC2L affects the leaf development by regulating the auxin content. Conclusions These results suggest that LcCUC2L may play a critical role in leaf development and morphogenesis in L. chinense, and our findings provide insight into the molecular mechanisms of leaf development in L. chinense.
Keywords: Liriodendron Chinense; Leaf development; Cotyledon; Rosette leaf; LcCUC2-like